Ever Approachable Never Attainable : Science Religion Dialogue in India - Kuruvilla Pandikattu (Pune Creati Ventures, 2015)
What is really the significance of dialogue between science and religion in India today? How can it foster better cooperation and sustainable life among human communities? What is the relevance of science-religion dialogues in our context? These are some of the questions this book takes up and deliberates. Assuming that dialogue between science and religion is no more an option but an obligation. This book takes us this venture critically and creatively. First it explores the challenges of and opportunities for science-religion dialogue from Indian perspectives. Then it explores human nature as something ever approachable. Finally, it explores the ever-elusive nature of human (and divine) nature as never attainable. This title of the book, thus, indicates the ever fascinating and elusive nature of the world, human beings, and God.
Keywords: Religion; Science